1999
DOI: 10.1111/j.2042-3306.1999.tb05263.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting accumulation of lactate in red blood cells

Abstract: Summary In horses, both the post exercise distribution of lactate between plasma and red blood cells (RBC) and the activity of lactate transporters on the RBC membrane vary widely between individuals. In this study, we investigated the effects of pH, time and temperature on lactate distribution in vitro, and compared the in vitro activity of lactate transporters with the accumulation of lactate into RBC in vivo. To accomplish this, we took venous blood samples at rest and after trotting races. The post exercis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
40
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 15 publications
7
40
0
Order By: Relevance
“…Up to 50% of the total lactate can be found in red blood cells of horses after intense exercise, and therefore, it is speculated that the red blood cells are responsible for re-ducing the concentration of blood lactate levels during maximal exercise (Pösö et al 1995, Väihkönen et al 1999. The lactate influx into the erythrocytes may be influenced by various factors and becomes greater with lower pH and increased temperature (Väihkönen et al 1999). Lactate can enter the erythrocytes by three routes (Poole & Halestrap 1993), (1) free diffusion of acids not dissociated, (2) monocarboxylate transporters (MCTs), or (3) protein band 3 (anion exchanger 1, AE1).…”
Section: Bioenergeticsmentioning
confidence: 99%
“…Up to 50% of the total lactate can be found in red blood cells of horses after intense exercise, and therefore, it is speculated that the red blood cells are responsible for re-ducing the concentration of blood lactate levels during maximal exercise (Pösö et al 1995, Väihkönen et al 1999. The lactate influx into the erythrocytes may be influenced by various factors and becomes greater with lower pH and increased temperature (Väihkönen et al 1999). Lactate can enter the erythrocytes by three routes (Poole & Halestrap 1993), (1) free diffusion of acids not dissociated, (2) monocarboxylate transporters (MCTs), or (3) protein band 3 (anion exchanger 1, AE1).…”
Section: Bioenergeticsmentioning
confidence: 99%
“…Based on the results from previous studies (Väihkönen and Pösö 1998;Väihkönen et al 1999Väihkönen et al , 2001), horses were classified into 2 groups based on their lactate transport activity (nmol/mg x min) measured at 10 mmol/l lactate concentration; low (LT) activity with ≤ 1 and high (HT) activity with >1. In the sample, 24 of the 101 horses (24%) were classified as LT.…”
Section: Mode Of Inheritance For Lactate Transport Activitymentioning
confidence: 99%
“…The role of MCT and AE1 in lactate transport can be studied by use of inhibitors (Skelton et al 1995;Väihkönen and Pösö 1998;Väihkönen et al 1999Väihkönen et al , 2001) and our previous studies have shown convincingly that interindividual variation is due to variation in MCT activity. The difference in transport activity is also reflected in vivo; after maximal exercise (trotting race), the lactate concentration in RBC of HT horses is higher than that of LT horses (Väihkönen et al 1999).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations